Caracterización de un modelo de negocio de banca digital en el contexto colombiano (2020)
This final work is based on the research question: What would the digital banking business model that could be applied in the financial sector in Colombia? To carry out it, exploratory research was done using a methodological design formed that by three phases. In the first phase: Building of the conceptual framework, based on Systematic Review of Literature (RSL) for identifying the main concepts. In the second phase: Colombian Context analysis description, through the PESTEL analysis, several documentary sources of the financial system in the Colombian context were studied. In the third phase: Characterization of the main attributes that the digital banking business model should have in the country, based on each one of the characteristics of the modules of the business models, that were identified during the RSL, and the previous context analysis. To represent this business model, the characterization’s results were diagrammed according to the business model canvas. As a result of this research, we obtained: 1) A good comprehension of the different concepts that refer to digital transformation, internet banking, mobile banking and business models. 2) An overview of the Colombian environment focused on the financial system and digital transformation, reviewing the political, economic, social, technological, legal and environmental aspects, and 3) A set of attributes of value proposition, market segments, customer relationships, channels, activities, resources and key associations that are useful for the proposal of the business model for digital banking in the context of Colombia. Thus, the main contribution of this research is the proposal of a digital banking business model for Colombia.